2018 IEEE/ACM International Conference on Utility and Cloud Computing Companion (UCC Companion) 2018
DOI: 10.1109/ucc-companion.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FaaS Orchestration Systems

Abstract: Since the appearance of Amazon Lambda in 2014, all major cloud providers have embraced the "Function as a Service" (FaaS) model, because of its enormous potential for a wide variety of applications. As expected (and also desired), the competition is fierce in the serverless world, and includes aspects such as the run-time support for the orchestration of serverless functions. In this regard, the three major production services are currently Amazon Step Functions (December 2016), Azure Durable Functions (June 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 5 publications
0
32
0
1
Order By: Relevance
“…Numerous works evaluate commercial and open source FaaS solutions [11,15,17] focusing on analysis of supported features and comparison based on the identified feature sets. Leitner et al [16] presents a mixed-method empirical study focusing on FaaS development in industrial practice, which combines a gray literature analysis with interviews and online questionnaire.…”
Section: Related Workmentioning
confidence: 99%
“…Numerous works evaluate commercial and open source FaaS solutions [11,15,17] focusing on analysis of supported features and comparison based on the identified feature sets. Leitner et al [16] presents a mixed-method empirical study focusing on FaaS development in industrial practice, which combines a gray literature analysis with interviews and online questionnaire.…”
Section: Related Workmentioning
confidence: 99%
“…During our studies we also found that a large portion of the integration services based on serverless orchestration make heavy use of FaaS and act as a layer of abstraction to the service. An example of such a service would be AWS Step Functions [11,21].…”
Section: -Integrationmentioning
confidence: 99%
“…General-purpose serverless orchestration frameworks include AWS Step Functions [6], Azure Durable Functions [7], Fission Workflows [14], and HyperFlow [16,47]. But these frameworks are not well-suited for supporting large, complex jobs, because they require manual workflow configurations (e.g., JSON) [46].…”
Section: Related Workmentioning
confidence: 99%